Stabilizacyjne funkcje narzędzi polityki handlowej i ich wykorzystanie w polityce transformacji systemowej w Polsce - Domiter, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
A key policy contributing to the establishment of a market economy has been the liberalization of international trade, and the welcome given to foreign investment. Poland quickly took steps to open up its economy after the fall of communism. The goal of joining the EU and becoming part of its single market was formally confirmed in 1991 with Poland's signature, alongside other central European countries, of the Association Agreement (the Europe Agreement) with the EU, which entered into force in February 1994. The trade-related part of this agreement, which entered into force in 1992, provided for the gradual establishment of free trade in industrial products between Poland and the EU, and reciprocal concessions in agriculture. Tariffs and quantitative restrictions on imports of most industrial goods were eliminated by January 1995 on the EU side and by January 1999 on the Polish side. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 87-95